ANALISIS KELENGKAPAN UNSUR DAN POLA PENALARAN PARAGRAF PADA BERITA UTAMA SURAT KABAR HARIAN KOMPAS - Tasyrifin Tasyrifin; Usman Usman (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
Analysis of the Completeness of the Paragraph Reasoning Elements and Reasoning Patterns in the Headlines of Kompas Daily Newspapers. This study aims to determine the completeness of the elements and paragraph reasoning patterns in Kompas daily headlines. This type of research is a qualitative descriptive study. The data source of this research is Kompas daily newspaper. The results showed that the elements of the paragraphs used in Kompas daily headlines were the main sentence elements, explanatory sentences, affirmative sentences, and transitions, and used deductive, inductive, and mixed paragraph reasoning patterns. The paragraph elements used in Kompas daily headlines are complete and there are all patterns of reasoning in his writings, although more often use deductive patterns.